Colonic dilation is associated with increased central line associated blood stream infection for patients with intestinal failure - Pamela Emengo; Shweta S. Namjoshi; James C.Y. Dunn (Intestinal Failure, 2025)
Introduction: Management of intestinal failure involves supplemental nutrition and complication minimization to achieve enteral autonomy. Previous research to identify prognostic factors in IF focused on the small bowel, yet little work has been done to associate the colon with IF outcomes. We hypothesize that like small bowel dilation, colonic dilation is associated with intestinal failure morbidity. We also investigate whether a standardized colonic diameter ratio differs from the maximal colonic width in predicting outcomes in children with intestinal failure. Material and methods: We conducted a retrospective cohort study of all children with gastrointestinal contrast imaging and intestinal failure in our intestinal rehabilitation program between 2013 and 2023. Medical records were reviewed for patient information and imaging review. A colonic diameter ratio was calculated by dividing the maximal colonic diameter by the height of the fifth lumbar vertebra. Results: Thirty-two patients were assessed based on colonic width and colonic diameter ratio. The median age of patients was 7.0 years (IQR 3 – 11 years). Maximum colonic width correlated positively with age, catheter-associated bloodstream infection, and parenteral nutrition duration. Colonic diameter ratio, on the other hand, did not show a significant correlation with age or parenteral nutrition duration, but had significant positive correlations with catheter-associated bloodstream infection. Conclusion: Maximum colonic width was significantly associated with increased morbidity in patients with intestinal failure. Increased colonic dilation after normalization by the size of the patient is associated with increased central line associated bloodstream infections.